Hiatal hernia: A rare cause of tracheal stenosis - Hiroshi Ito; Ryoko Ogawa; Nobutake Shimojo (JEM Reports)
Background: Although hiatal hernia is a benign disease, it can sometimes cause cardiopulmonary complications. Case report: We report an 86-year-old Japanese woman brought to the emergency department because of sudden-onset dyspnea and barking coughs after lunch. Chest computed tomographic images showed a stenosed trachea sandwiched between the hiatal hernia with the food bolus and the right common carotid artery. She underwent esophagus decompression using a nasogastric tube, and her symptoms resolved immediately. “Why should an emergency physician be aware of this?”: Hiatal hernia can be a rare cause of respiratory symptoms, even if the hiatal hernia is not massive. Such condition can be treated by esophagus decompression using a nasogastric tube.